Analisa Efisiensi Badan Amil Zakat Nasional (BAZNAS) Sebelum dan Pada Saat Pandemi Covid-19 - Hidayatullah, Nurul; Nurullaily, Shulhah (Journal of Islamic Economic Scholar, 2025)
Abstract One of the Amil Zakat Institutions in charge of collecting funds from the public and redistributing them is the Amil Zakat Institution (LAZ) or Amil Zakat Agency (BAZ). The existence of this institution aims to collect funds from the community in the form of zakat, infaq, sadaqah (ZIS) which will be redistributed to underprivileged people. This study aims to analyze the efficiency of the National Amil Zakat Agency (BAZNAS) in 2017-2021 before and during the co-19 pandemic based on financial reports taken from the official BAZNAS website using the Data Envelopment Analysis (DEA) method with variables of zakat revenue and employee expenditure as input variables and variables of zakat distribution as output variables. The results showed that the efficiency of BAZNAS's financial performance occurred in 2018 and 2021 and in 2017, 2019, and 2020 BAZNAS's financial performance could be said to be inefficient.